The resources of neurophysiological methods for diagnostic localization of nervous system lesion in children’s neuroinfections - V. N. Komantsev; N. V. Skripchenko; M. V. Savina (Журнал инфектологии)
The algorithms of neurophysiological diagnostic of impairment localization of nervous system in acute phase of neuroinfection in children were elaborated. The combined some EMG and evoked potentials methods were reliable for diagnostic botulism, polyneuropathy, mononeuropathy, polyradiculopathy, poliomyelitis, inflammation myelopathy, myelitis, meningitis, encephalitis. The reliability of neuriphysiologic diagnostic was 81–93%.